Nutrient Pollution and Its Dynamic Source-Sink Pattern in the Pearl River Estuary (South China) - Tao, Wei; Niu, Lixia; Dong, Yanhong; Fu, Tao; Lou, Quansheng (Frontiers in Marine Science, 2021)
Nutrient enrichment and its quantitative source-sink chains of the biogeochemical processes, highly co-influenced by natural changes and anthropogenic disturbances, have scarcely been documented in the Pearl River Estuary (China). Field investigations of nutrient samples taken between 1996 and 2018 showed significant differences in nitrogen and phosphorus with times and sites. The concentrations of DIN and DIP gradually increased over the past two decades, with good fitted linear curves (R= 0.56 for DIN, R= 0.92 for DIP); while the temporal variation in DSi was non-significant. The nutrient concentrations decreased from the land to the sea. Human-induced activities have resulted in significant changes in nutrient concentrations and their forms. The aquatic environment was highly sensitive to nutrient pollution and eutrophication risk, which accordingly corresponded to high phytoplankton production (chlorophyll-a > 10 μg/L) and biodiversity. Phosphorus was the limiting factor of phytoplankton growth in this estuary (N/P >> 16), and more frequently caused the eutrophication risk and blooms. Heavy eutrophication (> 5) was detected in the inner Lingdingyang bay, classified as severe eutrophic. The environmental quality assessment indicated that the whole estuary was ranked as sub-healthy. The nutrient pollution was largely influenced by riverine input, quantified by PCA-generation, and the contributions of coastal emission and atmospheric deposition were followed. The two-end member mixing model differentiated the physical alterations from the biological activity and identified the dynamic source-sink patterns of nutrient species. These results suggested that nutrient production and biological uptake co-occurred in the upper and middle estuary (salinity < 20‰), while nutrient removal was mainly dominated in the lower estuary (salinity > 20‰). Nitrogen and silicate had relatively conservative behaviors in the estuary and phosphate showed an active pattern.